Etos Kerja dalam Manajemen Pendidikan Islam Menurut Tafsir Al-Wahidi (Kitab Al-Basit) terhadap Surat At-Taubah ayat 105 - Putri Hidayatul Azizah; Denas Hasman Nugraha (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Islamic educational management is an important aspectof the development of educational system incorporanting religious values, morality and ethics. The work ethic of islami education management refers to the concept of combining learning, practice and behavior in accordance with Islamic teachings. An important reference in the analysis of work ethics in Islamic educational management is Tafsir Al-Wahidi (Kitab Al-Basith) on surah At-Taubah, verse 105. The research uses literature studies as a method of collecting data, adopting a qualitative research approach of descriptive and interprenting nature. The interpretation of the surah at-taubah verse 105, according to Al-Wahidi teaches the ethics of work for leaders and managers in the field of education management. Tafsir Al-Wahidi emphasizes the importance of taking into account various factor and perspectives when making decisions, as well asassesing the interests of users. Decisions should be made wisely and fairly and resources should be managed according to user needs. These cocepts serve as a guide for leaders and managers in establishing management system thst peomote good moral and ethical values and ensure participation and fairness.d